GINS4 might be a novel prognostic immune-related biomarker of not only esophageal squamous cell carcinoma and other cancers - Donghui Jin; Ligong Yuan; Feng Li; Shuaibo Wang; Yousheng Mao (BMC, 2022)
Abstract Background Immunotherapy using immune checkpoint inhibitors (ICIs), such as antibody of programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) has showed as a promising treatment for esophageal squamous cell carcinoma (ESCC), but resistance is unavoidable. This study aimed to find more immune-related genes to promote the efficiency of immunotherapy. Materials and methods Three datasets were downloaded from Gene Expression Omnibus (GEO) database. Gene differential analysis was performed to identify differentially expressed genes (DEGs), then ceRNA network was constructed based on differentially expressed lncRNAs and mRNAs. Next, Functional enrichment analysis and protein-protein interaction (PPI) network were built to reveal the potential function of mRNAs in ceRNA network. Survival analysis and immune cell infiltration level analysis were utilized to identify prognostic immune-related genes. Finally, pan-cancer analysis was performed to show the role of immune-related genes in other cancers. Results The data of 215 samples in total were obtained from GEO database (98 normal tissues and 117 tumor tissues), and 1685 differentially expressed mRNAs (176 downregulated and 1509 upregulated) and 3 upregulated lncRNAs (MCM3AP-AS1, HCP5 and GUSBP11, all upregulated) were found. ceRNA network was constructed to reveal some special correlation. Function enrichment showed some potential functions of mRNAs in ceRNA network such as mitotic cell cycle process, negative regulation of DNA-binding transcription factor activity, ossification, VEGFA-VEGFR2 signaling pathway, epithelial to mesenchymal transition, embryonic morphogenesis and so on. PPI network showed the physical interactions between each mRNA in ceRNA network. Through survival analysis and immune cell infiltration level analysis, GINS4 was confirmed as an immune-related prognostic gene in ESCC. GSEA showed some potential functions such as negative regulation of monocyte chemotaxis, antigen processing and presentation of endogenous peptide antigen via MHC class I via ER pathway, positive regulation of antigen processing and presentation, dendritic cell antigen processing and presentation and so on. Finally, pan-cancer analysis revealed that GINS4 might be a novel immune-related prognostic gene in ESCC and other cancers. Conclusion Our study suggested that GINS4 was correlated with prognosis and immune cell infiltration level of ESCC and other cancers. It may deserve further investigation as a potential immune-related prognostic biomarker of ESCC and other cancers.